The of Effect Instructional Design based on Kagan Structure In Generating Information Skills for First Intermediate Student’s In Mathematics (Journal Of Educational and Psychological Researches, 2019)
The aim of the research is to identify the effect of instructional design according to Kagan structure among the first intermediate school student’s, and how skills could help in generating information in mathematics. In accordance with the research objectives, the researcher has followed the experimental research method by adopting an experimental design with two equivalent groups of post-test to measure skills in generating information. Accordingly, the researcher raised two main null hypotheses: there were no statistically significant differences at the level of significance (0.05) between the average scores of the experimental group who studied the material according to Kagan structure and the scores of control group students who studied through the ordinary method in generating information skills. The population of the research was limited to the first intermediate students at Al-Karkh-1 directorate in Baghdad City, in which (80) students were chosen from Al-Mustafa intermediate school for boys, distributed into two equal groups. The equivalence between the two research groups was conducted statistically in the variables of (age, the previous achievement of mathematics, skills of generating information, intelligence, and previous information). In order to achieve the objectives of the research and collecting specific data relating to the experience , test  were made according to the following : Test of generating information skills consists of ( 16 ) paragraphs, an article distributed among  the four skills for producing information in the amount of ( 4 ) paragraphs for each skill(fluency, flexibility, setting hypothesis, Data prediction). To analyze the collected data, the researcher used the Pearson correlation coefficient,Kuder–Richardson -20 equation, T-test for two equivalent and independent samples. the results indicated a statistically significant difference for the experimental group who studied the material according to Kagan structure in total generating information skills, the researcher has reached a set of conclusions, such as; teaching according to design basing on Kagan structure has an effect in generating information. The study came out with a number of suggestions and recommendations.  Keyword: instructional design, Kagan structures, Skills, generating information